Sequenciamento completo e estrutura cristalográfica da metaloprotease leucurolisina-a purificada do veneno de Bothrops leucurus - Rodrigo Novaes Ferreira (2009)
Leucurolysin-a (leuc-a) is a P-I class snake venom metalloproteinase (SVMP) from the venom of Bothrops leucurus, a poisonous snake which is responsible for the majority of snakebites in the northeast of Brazil. It has been shown that leuc-a degrades fibrin clots directly in vitro without activating plasminogen (Pg), and does not elicit any hemorrhagic response. Leuc-a is a single chain zinc binding endopeptidase composed of 202 amino acids residues, which shows high similarity with other P-I SVMPs. In this work, leuc-a was crystallized using the hanging-drop vapour-diffusion method. Two data set were collected,one with 1.8 A, and other with 1.6 A. Data sets showed that the crystals belongs to the orthorhombic P212121 space group, with unit-cell parameters very similar. The crystallographic structure of leuc-a was solved by Molecular Replacement technique using the Bothrops asper metalloproteinase (BaP1) structure (PDB code 1ND1) as template.Leuc-a model was refined to a final Rfactor of 0.168 and Rfree of 0.235 against diffraction data of 1.80 A of resolution. The structure displayed the zinc binding motif H142E143XXH146XXG149XXH152 as well as the C164I165M166 motif ( gMet-turn h), which characterize the metzincin superfamily of metalloproteinases. A Zn2+ ion was observed inthe active site cleft of the enzyme and one structural Ca2+ ion was assigned on the molecular surface close to its C-terminal. The Zn2+ ion was tetra-coordinated by three imidazole NÃ2 atoms from H142, H146 and H152 and one catalytic water molecule anchored to the side-chain carboxyl group of E143. Leuc-a has six cysteine residues involved in threedisulfide bridges (Cys117-Cys197, Cys157-Cys164, and Cys159-Cys181). The other data set, with 1.6 A of resolution, was was refined to a final Rfactor of 0.178 and Rfree of 0.231. This model showed a unknown electron density at active site. This ligand was identified, synthesized and tested with leuc-a. The results showed a inhibition of proteolitic activity leuc-a over dimethyl casein.